Specific Notarial Protection of the Testator's Exclusive Rights: Kazakh and International Experience - JUMABAYEVA, Karlygash Asilkhanovna; TATARINOVA, Lola Furkatovna; ALAYEVA, Gulnaz Tursunovna; SULEIMENOVA, Saule Zhusupbekovna; TATARINOV, Danila Vladimirovich (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).11, 2019)
This study is concerned with one of the most burning issues of intellectual property rights, namely the notarial protection of the testator's exclusive rights. The article analyzes the Kazakh and international experience in solving this issue. In the course of the study, the authors obtained the following results: - In legal practice, the non-acceptance of inheritance and refusal to inherit exclusive rights have their specific features; - It is proposed to supplement the existing civil legislation on the protection of the testator's copyrights. ‘Kazakhstan Authors' Society’ conducts its activities in the territory of the Republic of Kazakhstan. Its main function is to manage the property rights of authors. This management includes the issuance of permits to use deliverables on behalf of authors, as well as the collection, distribution and payment of royalties. It has been established that a notary has the right to apply to ‘Kazakhstan Authors' Society’ to determine one's authorship. The authors have revealed that the current Kazakh legislation does not state the creation time of some deliverable and does not provide for the notarial certification of a web page (in case of copyright infringement). Thus, a notary takes measures to protect the intellectual property rights owned by the copyright holder that might become the subject of succession.